Antioxidants, Anti-inflammation, Anti-hyperglycemia and Chemical Evaluation of the whole plant extracts of Anisopus mannii N.E.Br. - Muhammad Usman; Mahmoud Dogara Abdulrahman; Hamad, Saber; Hama, Harmand A.; Lema, Abubakar Abdullahi (Zanco Journal of Pure and Applied Sciences, 2022)
Anisopus mannii from the family Asclepiadaceae is a perennial herb that is currently utilized in the traditional Northern Nigerian medicinal system. The study document comprehensive In Vitro biological evaluation and chemical profiling of A. mannii whole plant crude extracts. Qualitative phytochemical, antioxidants, anti-inflammation, anti-hyperglycemia and chemical profiling was determined. The results revealed the presence of phenols, alkaloids, tannins, glycosides flavonoids, and saponins. The plant has the inhibition capacity to convert Fe3+ to Fe2 at 18.9 mmol/gm, scavenging at 75.5, injured tissues 28.4 75.5, -amylase 62.7 and α-Glucosidase 89.5 µg /mL respectively. 9-Octadecenoic acid, methyl and Lup-20(29)-en-3-ol, acetate, (3. beta) are the major compounds found in the whole plant extract. The current groundbreaking research revealed ethanolic extract from the whole plant is an effective medicinal agent. It provides the possibility for different therapy regimens to be developed from it. Research is needed to discover and purify the active chemicals that are responsible for therapeutic efficacy.